EMPOWERING INDIVIDUALS FOR FUTURE SUCCESS THROUGH LIFE SKILLS AND VOCATIONAL TRAINING IN INDIA - Vemula, Muttu; L.K., Lalbiakfeli (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the rapidly changing global environment of today, education has expanded beyond its historical purview of teaching fundamental academic disciplines. It has developed into a dynamic platform that needs to give people a broad range of skills, including both life and career training, in order to prepare them for success in an uncertain future. This paradigm change is particularly important in a nation like India, where young make up the majority of the population. Comprehensive training programs that cover both personal development and practical skills are desperately needed in order to take advantage of this demographic advantage and close the skill gap. This article examines the critical importance of vocational training and life skills in India and how they can support the country’s overall development and prosperity. It also explains how important it is for training programs and educational institutions to recognize and give priority to the integration of life skills in order to ensure that students are fully equipped for success in the fast-paced world of today.